2013
DOI: 10.1186/1471-2407-13-280
|View full text |Cite
|
Sign up to set email alerts
|

Potentiality of a triple microRNA classifier: miR-193a-3p, miR-23a and miR-338-5p for early detection of colorectal cancer

Abstract: BackgroundMicroRNAs (miRNAs) are short, non-coding RNA molecules that act as regulators of gene expression. Circulating blood miRNAs offer great potential as cancer biomarkers. The objective of this study was to correlate the differential expression of miRNAs in tissue and blood in the identification of biomarkers for early detection of colorectal cancer (CRC).MethodsThe study was divided into two phases: (I) Marker discovery by miRNA microarray using paired cancer tissues (n?=?30) and blood samples (CRC, n?=?… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
115
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(125 citation statements)
references
References 61 publications
9
115
0
1
Order By: Relevance
“…41 MiR-193a-3p was found to be significantly up-regulated in both tissue and blood samples of colorectal cancer patients, and there was an increasing trend of expression of circulating miR-193a-3p in advanced stages of colon cancer patients compared with healthy individuals. 42 Up-regulation of miR-193 was also found in the high-grade prostate tumors (Gleason score ≥8) 43 as well as in serum samples obtained from patients with esophageal squamous cell carcinoma. 44 In apparent contrast with these findings but in agreement with those of this study, in lung and oral squamous cell carcinoma, 45,46 acute myelogenous leukemia, 47 breast cancer, 48 and Wilms' tumor, 49 circulating miR-193a-3p levels were found to be reduced in plasma of patients compared with healthy controls.…”
Section: Discussionmentioning
confidence: 97%
“…41 MiR-193a-3p was found to be significantly up-regulated in both tissue and blood samples of colorectal cancer patients, and there was an increasing trend of expression of circulating miR-193a-3p in advanced stages of colon cancer patients compared with healthy individuals. 42 Up-regulation of miR-193 was also found in the high-grade prostate tumors (Gleason score ≥8) 43 as well as in serum samples obtained from patients with esophageal squamous cell carcinoma. 44 In apparent contrast with these findings but in agreement with those of this study, in lung and oral squamous cell carcinoma, 45,46 acute myelogenous leukemia, 47 breast cancer, 48 and Wilms' tumor, 49 circulating miR-193a-3p levels were found to be reduced in plasma of patients compared with healthy controls.…”
Section: Discussionmentioning
confidence: 97%
“…These results suggest that miR-193a-3p may be involved in the pathogenesis of lung cancer as a tumor suppressor. Indeed, miR193a-3p has been reported in many studies to be down-regulated in cancers (31,33,38,52,54,55). On the other hand, it is well known that a single miRNA can target multiple genes, whereas multiple miRNAs can target a single gene.…”
Section: Discussionmentioning
confidence: 99%
“…miR-101, miR-124, and miR-139 were found to be frequently down-regulated in this disease, and using this approach, the latter was determined to be a key tumor suppressor in early cancer development. Using a microarray, Yong et al (2013) identified seven miRNAs differentially expressed in both CRC tissue and blood samples, and indicated that the triple miRNA classifier comprising miR-193a-3p, miR-23a, and miR-338-5p is a potential blood biomarker for early CRC detection. According to various miRNA-profiling studies, several miRNAs have been validated as potential oncogenes or tumor suppressor genes in CRC.…”
Section: Differentially Expressed Mirnas In Crcmentioning
confidence: 99%